2013
DOI: 10.1002/adma.201302215
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Macromolecular Self‐Assembly: From Biomimetic Chemistry to Bio‐Inspired Materials

Abstract: Macromolecular self-assembly (MSA) has been an active and fruitful research field since the 1980s, especially in this new century, which is promoted by the remarkable developments in controlled radical polymerization in polymer chemistry, etc. and driven by the demands in bio-related investigations and applications. In this review, we try to summarize the trends and recent progress in MSA in relation to biomimetic chemistry and bio-inspired materials. Our paper covers representative achievements in the fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
181
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(182 citation statements)
references
References 291 publications
0
181
0
Order By: Relevance
“…[13][14][15] To date, among the amounts of drug carriers, polymeric micelles have been widely employed in the development of multidrug co-delivery systems due to many advantages, such as core-shell nanostructures, excellent biocompatibility, biodegradability and versatile chemistry for further functionalization. 16,17 In addition, they are of nanoscopic size and stealthy property. Thus, polymeric micelles usually lead to a prolonged blood circulation and passive accumulation in solid tumor through the enhanced permeability and retention effect.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] To date, among the amounts of drug carriers, polymeric micelles have been widely employed in the development of multidrug co-delivery systems due to many advantages, such as core-shell nanostructures, excellent biocompatibility, biodegradability and versatile chemistry for further functionalization. 16,17 In addition, they are of nanoscopic size and stealthy property. Thus, polymeric micelles usually lead to a prolonged blood circulation and passive accumulation in solid tumor through the enhanced permeability and retention effect.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Research has focused on the spatiotemporal behavior of molecular assembly and, especially, the dynamics of these materials when utilized in life systems 4,5 and soft devices. 6,7 Various experimental and theoretical studies on assembly behavior have been reported and reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient examples are the large ribosomal heterocomplex, myosin filaments, crystalline bacterial S layers 1 and membranes containing 2D arrays of bacteriorhodopsin or porins 2 . In selfassembly studies with protein building blocks, various nanostructures, including vesicles and cages, fibres and tubes, and lattice patches on surfaces, have been reported [3][4][5][6][7][8] . However, discrete multidimensional architectures, that is, protein crystalline frameworks (PCFs) with regular lattice structures, are still rare compared with the large number of proteins.…”
mentioning
confidence: 99%